Effect of process parameters on solvolysis liquefaction of Chlorella pyrenoidosa in ethanol–water system and energy evaluation. (1st June 2016) - Peng, Xiaowei; Ma, Xiaoqian; Lin, Yousheng; Wang, Xusheng; Zhang, Xiaoshen; Yang, Cheng
Highlights: Microalgae liquefaction in ethanol–water promoted bio-oil yield and property. There existed synergistic effect between ethanol and water. Ethanol contributed to deoxygenation and hydrogen-donating for bio-oil. Net energy ratios of 20% and 40% ethanol were larger than pyrolysis technology. Abstract: In this work, Chlorella pyrenoidosa was converted into bio-oil via solvolysis liquefaction in sub/supercritical ethanol–water system. The influence of reaction temperature (220–300 °C), retention time (0–120 min), solid/liquid ratio (6.3/75–50.0/75 g/mL) and ethanol content (0–100%) on bio-oil yield and property was investigated. The increase of reaction temperature and retention time both improved the bio-oil yield. The bio-oil yield increased firstly and then decreased when the solid/liquid ratio and ethanol content exceeded 18.8/75 g/mL and 80%, respectively. As the reaction temperature <260 °C and retention time <30 min, a soft and unsticky product was insoluble in dichloromethane (DCM) during the extraction process. The chemical composition of the DCM-insoluble product was analyzed by FTIR (Fourier Transform Infrared Spectrometry). The change tendency of O/C and H/C atomic ratio of bio-oil indicated that the addition of ethanol contributed to deoxygenation and hydrogen-donating for bio-oil, due to the dehydration and decarboxylation reaction. 1 H NMR (hydrogen-1 nuclear magnetic resonance) analysis indicated that the main chemical compositions of bio-oil were aliphatic functional groups and heteroatomic functionalities (80.00–83.58%). The addition of ethanol enhanced the transesterification to form more ester. The NER (net energy ratio, the ratio of energy output to energy consumption) of solvolysis liquefaction in ethanol–water system (NER < 1) was less than that of hydrothermal liquefaction in sole water system (NER = 1.29), but the NERs of 20% and 40% ethanol content (NER = 0.91, 0.70 for 20% and 40% ethanol content) were larger than pyrolysis technology (NER = 0.66). The high bio-oil yield, better bio-oil property and high NER were achieved at reaction temperature of 300 °C, with retention time of 60 min, solid/liquid ratio of 18.8/75 g/mL and ethanol content of 40% (bio-oil yield = 39.75%, HHV (higher heating value) = 39.31 MJ/kg and NER = 0.70).